2014
DOI: 10.1186/1749-7922-9-31
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Canadian CT head rule and the new orleans criteria in patients with minor head injury

Abstract: AimThe aim of the study was to compare the New Orleans Criteria and the New Orleans Criteria according to their diagnostic performance in patients with mild head injury.MethodsThe study was designed and conducted prospectively after obtaining ethics committee approval. Data was collected prospectively for patients presenting to the ED with Minor Head Injury. After clinical assessment, a standard CT scan of the head was performed in patients having at least one of the risk factors stated in one of the two clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 15 publications
0
23
1
4
Order By: Relevance
“…Kavalci et al [14,15] and Durdu et al [16] reported that the most common trauma mechanism was motor vehicle accident. Our study also found that out-of-vehicle traffic accident was the most common cause of head trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Kavalci et al [14,15] and Durdu et al [16] reported that the most common trauma mechanism was motor vehicle accident. Our study also found that out-of-vehicle traffic accident was the most common cause of head trauma.…”
Section: Discussionmentioning
confidence: 99%
“…40,55,56 Although only some of these rules were fully validated, as outlined previously, most comparative analyses have shown very little difference among them in terms of predictive value. [57][58][59][60][61][62][63] Those that reported important differences tend to be small series. It should be noted that relatively large populations are needed to fairly compare rule application in cases in which intracranial lesions with clinical impact are so uncommon.…”
Section: Neurosurgical Clinical Prediction and Decision Rulesmentioning
confidence: 90%
“…3 There is debate on the indication of CT scan, however in Pakistan most hospitals perform CT scan in patients having mild or moderate traumatic brain injury. 18,19,20 In our center the neurosurgery residents and neurosurgeons order CT scans for all the patients having symptoms of neurological injury, cerebral edema, bleeding from orifices such as ears, oral and nasal cavity, GCS score less than 15 at the time of arrival with an additional sign and symptom of traumatic brain injury.…”
Section: Discussionmentioning
confidence: 99%